Culture and Language Learning in Higher Education - Byram, Michael, Ed (Multilingual Matters Ltd, 1994)
A collection of papers concerning cultural studies within college and university second language programs, particularly for foreign students, includes program descriptions from a variety of countries and discussions of cultural education and cultural conflict. Themes include the nature of cultural teaching, cultural education as a discipline, innovations in cultural education, fieldwork as an instructional approach, reflection on one's own culture as a result of foreign culture study, students of culture as teachers, and specific teaching methods. Papers include: "The Case of 'Landeskunde': A Vicious Circle?" (Dieter Kerl); "Cultural Studies and Student Exchange: Living the Ethnographic Life" (Celia Roberts); "Civilisation/Cultural Studies in Grenoble" (Jean-Paul Revauger);"Cultural Studies in English Studies: A German Perspective" (Jurgen Kramer); "Documentary Analysis in 'Civilisation' Studies: The French Approach" (Francois Poirier); "New Cultural Studies at Warwick University" (Peter Breen); "International Cultural Studies at Roskilde University" (Karen Risager); "From NIMBY Landeskunde to IMBY Cultural Studies" (Harald Husemann); "British Studies in English Language Teaching"(Edward G. Woods); and "Communication in Foreign Lands: The Cause, Consequences and Cures of Culture Shock" (Adrian Furnham). (MSE)